Effect of the Energy Transition on Food Security: The Role of the Female Agricultural Workforce in WAEMU Countries - Angbonon Eugene Kamalan; Assande Pierre Kadjo; Kouakou Romaric Kouame (European Scientific Journal, ESJ, 2025)
This study analyses the role of women in the relationship between the energy transition and food security in the 8 WAEMU countries (1996-2022). The use of an ARDL model shows that the energy transition significantly and symmetrically improves food security in the short term, but has a negative and asymmetric effect in the long term. The interaction between the energy transition and the female agricultural workforce has a positive effect in the long term, but is neutral in the short term. We recommend maximising short-term benefits and actively involving women in agriculture to improve long-term food security.